PENGARUH KEMANDIRIAN BELAJAR TERHADAP BERPIKIR KRITIS : BUKTI EMPIRIS PADA MATA KULIAH STATISTIK EKONOMI DAN BISNIS - Hamni Fadlilah Nasution; zulaika Matondang (As-Sulthan Journal of Education, 2026)
Critical thinking skills are a crucial competence in solving quantitative data phenomena in Economic and Business Statistics courses. However, the abstract nature of the course often triggers student dependence on lecturers. This study aims to empirically examine the effect of self-regulated learning on students' critical thinking skills in the Economic and Business Statistics course. This associative quantitative research involved 76 students of the Islamic Economics Study Program at the Faculty of Islamic Economics and Business. Data were collected through self-regulated learning questionnaires and critical thinking skills tests, which were then analyzed using simple linear regression via SPSS software. The results showed that self-regulated learning had a positive and significant effect on students' critical thinking skills. Self-regulated learning contributed 92.7% to the variation in critical thinking skills, while the remainder was explained by other factors outside the research variables. Indicators of self-regulation and initiative in seeking learning resources became the main drivers of students' sharpness in analyzing statistical data, evaluating hypotheses, and drawing valid economic inferences. The implications of this study emphasize the importance of lecturers designing project-based learning to stimulate learning autonomy while sharpening students' critical thinking skills